Different Shoulder Exercises Affect the Activation of Deltoid Portions in Resistance-Trained Individuals - Campos, Yuri A. C.; Vianna, Jeferson M.; Guimarães, Miller P.; Oliveira, Jorge L. D.; Hernández-Mosqueira, Claudio; da Silva, Sandro F.; Marchetti, Paulo H.
The aims of this study were to compare muscle activity of the anterior deltoid, medial deltoid, and posterior deltoid in the bench press, dumbbell fly, shoulder press, and lateral raise exercises. Thirteen men experienced in strength training volunteered for the study. Muscle activation was recorded during maximum isometric voluntary contraction (MVIC) for data normalization, and during one set of 12 repetitions with the load of 60% 1RM in all exercises proposed. One-way repeated-measures ANOVA with Bonferroni’s posthoc was applied using a 5% significance level. For anterior deltoid, the shoulder press (33.3% MVIC) presented a significantly higher level of activation when compared to other exercises. Also, no significant difference was found between the bench press (21.4% MVIC), lateral raise (21.2% MVIC), and dumbbell fly (18.8% MVIC). For the medial deltoid, the lateral raise (30.3% MVIC) and shoulder press (27.9% MVIC) presented a significantly higher level of activity than the bench press (5% MVIC) and dumbbell fly (3.4% MVIC). Besides, no significant difference was found between the bench press and the dumbbell fly. For the posterior deltoid, the lateral raise (24% MVIC) presented a significantly higher level of activation when compared to other exercises. For the posterior deltoid portion, the shoulder press (11.4% MVIC) was significantly more active than the bench press (3.5% MVIC) and dumbbell fly (2.5% MVIC). Moreover, no significant difference was found between the bench press and the dumbbell fly. In conclusion, the shoulder press and lateral raise exercises showed a higher level of muscle activation in the anterior deltoid and medial deltoid when compared to the bench press and dumbbell fly exercises.